The connections between art and science in Antarctica: Activating Science*Art. (23rd May 2019) - Stevens, Craig; O'Connor, Gabby; Robinson, Natalie
Abstract: Art may be made as a guide to understanding sense of place, and also as a pathway to understanding and valuing scientific ideas. Here we consider this connection in the context of a selected history of artists working in Antarctica, from early explorers to the modern era. This provides a parallel trajectory for the nature, realisation and purpose of the art. We then consider the interaction between art and science and the nature of interdisciplinary work by looking at work produced in a sea ice-based science field camp by an artist collecting data – both scientific and art focused. The artist participated in two field campaigns a year apart, allowing comparison of the evolution of both the artistic practice and the science data collection. Furthermore, the collection of data that served both needs provides a unique point of connection between two fields of endeavour, which are typically considered as separate.